The impact of the COVID-19 pandemic on the tourist mobility of residents from a large city: the example of the Retkinia housing estate in Łódź - Matczak, Andrzej; Cłapa, Krzysztof (Turystyka w badaniach podstawowych, 2023)
The aim of the study is to identify the impact of the COVID-19 pandemic on the level and nature of participation in tourism by the inhabitants of Retkinia – one of the largest housing estates in Łódź. This impact was examined by comparing the level and nature of participation in tourism during the pandemic (in 2020) with the period before it (in 2019). The research was based on an internet survey in the form of an in-depth interview. The survey contained 18 factual questions, 10 behavioral questions (regarding opinions on the impact of the pandemic on lives and tourist behavior) and 7 questions describing the demographic and socio-economic characteristics of the respondents. Based on the registered changes in the level and nature of participation in tourism in 2019–2020 and the opinions expressed by them, differences in tourist behavior caused by the pandemic were identified and the scope of protective measures taken by the surveyed inhabitants of Retkinia was indicated. The obtained results in general indicate similar changes trends in tourist behavior caused by the pandemic, found in many previous studies, but with some differences. They also indicate the limited undertaking of protective measures recorded in the participation and nature of tourist trips undertaken by respondents.